Erysiphe corylacearum as a new pathogen of hazelnut in the Czech Republic - Šafránková, Ivana (Plant disease, 2023)
In July 2021, leaves and shoot tops of the common hazel (Corylus avellana L.), with a whitish coating, were found in the Czech Republic (southern Moravia region). The infected hazel bushes were found along a road in a deciduous forest and in an urban garden. In most European countries, Phyllactinia guttata is found on the abaxial surface of the leaves in the form of a continuous whitish to light grey mycelium, possibly with large black chasmothecia. In our case, the mycelium was present on both sides of the leaves, but the symptoms and the incidence were much stronger on the adaxial side. The first symptoms usually appeared on the adaxial side of the leaves as small white radially expanding patches of mycelium. In the final stage, the spots merged and covered a substantial part of the leaf blade (50-85 % on the adaxial side, 5-25 % on the abaxial side). When the abaxial side of the leaves was infected, chlorotic spots were evident on the adaxial side. The spots of powdery mildew were small (3-15 mm), whitish, rounded to irregular, effuse eventually becoming confluent, and occurred primarily on the adaxial side of the leaves. Conidiophores (30-53×4-6 µm) grew on the amphigenic mycelium, were erect, consisted of 1-3 cells, i.e. cylindrical foot cell and followed 1-2 cells, from which hyaline ellipsoid to doliform-limoniform conidia (17-34 ×15-21) (n = 50) were individually detached. Single or in groups dark brown chasmothecia (77-116 µm in diameter) had up to hyaline 8-15 aseptate straight appendages (50-102 µm) with multiple (3-5×) dichotomously branched apexes and recurved tips. Chasmothecia contained 3-6 asci (42-62 × 34-55 µm) with 4-8 obovoid to broadly ellipsoidal hyaline ascospores (14-22 × 75 µm). Based on morphological characters, the powdery mildew was identified as Erysiphe corylacearum (2). Morphological identification was confirmed by molecular analysis of samples. DNA was extracted from symptomatic leaves tissue using the DNeasy Plant Mini Kit, (Quiagen, Hilden, Germany) and the rDNA internal transcribed spacer region of 2 isolates was amplified using primers PMITS1 and PMITS2 (Cunnington et al. 2003) and sequenced. BLAST analysis of our 720bp fragments (both identical and represented by GenBank accession no. OR432526) showed 100% sequence identity to ITS rDNA sequences of E. corylacearum other countries of Central Europe for example from Austria (MW031866), Italy (MW045428), Hungary (OQ411007), Germany (OP554268) or Slovakia (MT176105). Pathogenicity was verified on two-year-old plants of Corylus avellana. Healthy leaves were artificially infected by dusting conidia from infected leaves. Inoculated plants were incubated under controlled conditions (21-23 °C, 70-80 % relative humidity). Characteristic symptoms of powdery mildew appeared on the adaxial side of the leaves 9-12 days after inoculation. Control plants treated with distilled water remained symptomless. Powdery mildew isolated from inoculated leaves was morphologically identical to isolates from naturally infected leaves. The first record of E. corylacearum in Europe on cultivated hazelnut species was reported by Sezer et al. (2017) in Turkey in 2013. Within a few years, the E. corylacearum spread and was recorded on various species of Corylus in other European countries (for example Mezzalama et al., 2020; Rosati et al., 2021; Beenken et al., 2022; Boneva et al., 2023), East Asia (Arzanlou et al., 2018) and the USA (Meparishvili 2019). To our knowledge, this is the first report of Erysiphe corylacearum in the Czech Republic